Autonomic protocol and architecture for devices in Internet of things - Ashraf, Qazi Mamoon; Habaebi, Mohamed Hadi; Sinnieh, Gopinath Rao; Ahmed, Musse Mohamud; Khan, Sheroz; Hameed, Shihab A. (2014)
With the advancement taking place in communication technologies, Internet of Things (IoT) is expected to play a major role in realizing smartness and functionality needed for applications such as Smart Homes and Electrical Smart Grids. However, in order to achieve that far reaching goal, select concepts of computing autonomy have to be suitably ported to IoT architecture. Recently reported works describe various frameworks, models and protocols for computing autonomy. Some others focus more on the practical implementation of autonomy using self-star (self-*) behavior in end nodes. This work proposes an autonomic architecture for IoT based on IBM’s autonomic framework. An accompanying protocol for service communication is also presented. Preliminary tests prove its suitability in an IoT environment from the perspective of energy conservation for the network.